A Review of Plants Used in South African Traditional Medicine for the Management and Treatment of Hypertension - Balogun, Fatai Oladunni; Ashafa, Anofi Omotayo Tom (Planta Medica, 2019)
South Africa contains 9% of the worldʼs higher plants, and despite its rich biodiversity, it has one of the highest prevalence of hypertension in Africa. This review provides information on medicinal plants embraced in South Africa for hypertension management, with the aim of reporting pharmacological information on the indigenous use of these plants as antihypertensives. This review not only focuses on the activity of antihypertensive medicinal plants but also reports some of its phytochemical constituents and other ethnopharmacological and therapeutic properties. Information obtained from scientific and or unpublished databases such as Science Direct, PubMed, SciFinder, JSTOR, Google Scholar, Web of Science, and various books revealed 117 documented antihypertensive plant species from 50 families. Interestingly, Asteraceae topped the list with 16 species, followed by Fabaceae with 8 species; however, only 25% of all plant species have demonstrated antihypertensive effects originating from both in vitro and in vivo studies, lending credence to their folkloric use. Only 11 plant species reportedly possess antihypertensive properties in animal models, with very few species subjected to analytical processes to reveal the identity of their bioactive antihypertensive compounds. In this review, we hope to encourage researchers and global research institutions (universities, agricultural research councils, and medical research councils), particularly those showing an interest in natural products, for the need for concerted efforts to undertake more studies aimed at revealing the untapped potential of these plants. These studies are very important for the development of new pharmaceuticals of natural origin useful for the management of hypertension.
Keywords: Amaryllidaceae; antihypertensive; Apiaceae; Asteraceae; Cucurbitaceae; Fabaceae; high blood pressure; Lamiaceae; medicinal plants; Rutaceae; South Africa